A STUDY ON THE READING SKILLS OF EFL UNIVERSITY STUDENTS - Flora Debora Floris (TEFLIN, 2009)
Abstract: The present study attempts to investigate kinds of reading skills that EFL (English as a Foreign Language) University students have difficulty with. For this purpose, two reading tests which covered seventeen kinds of reading skills were developed and administered to ten students of batch 2003 studying at an English Department of a private university in Surabaya, Indonesia. The analysis showed that each reading skill had different level of difficulty for the respondents..